Shakespeare im Spiegelkabinett - Zur produktiven Vielfalt seiner Rezeption - Alam, Sarah; Schaff, Barbara (Universitätsverlag Göttingen, 2016)
2014 and 2016, marked by the 450th anniversary of his birthday and the 400th anniversary of his demise respectively, have both been dedicated to the remembrance of William Shakespeare and the celebration of his work through readings, theater productions, movies, exhibitions, and many academic events. He is fondly called the "Bard" by many and has long been England's export hit. Shakespeare gained lasting fame and fortune during his lifetime not only by successfully moving his audience, but also because from the beginning his work inspired critical and artistic dialogue. The ingenuity and uniqueness of his work did not fail to inspire the creative imagination of successive generations of authors, artists, and musicians over the past four and a half centuries. In fact, each generation has reimagined and recreated Shakespeare in its own different way, bringing its own interpretation, themes, fashion, taste, and customs to the rereading, visualization, and intonation of his work. The brand "Shakespeare" is still as popular and productive as ever. A fact that is apparent not only in the huge numbers of visitors yearly to Stratford upon Avon and Verona, the city of Shakespeare's tragic-romance Romeo and Juliet, but also in the long line of movies produced based on his plays each year. One might even go as far as to assert that it is the generations of productive readers and their own unique creative interpretations that have kept the Bard alive over the past 450 years. This collection of essays celebrates Shakespeare's two big anniversaries and takes the opportunity to look at him from a different perspective, as a source of inspiration and, for a change, to explore the eclectic results of centuries of productive reception of his work from the Elizabethan era up to the 21rst century.